Carotid Endarterectomy and Stenting of the Internal Carotid Artery in Patients with Occlusion of the Contralateral Carotid Artery - N. S. Gorshkov; V. E. Ryabukhin; A. S. Koblik; L. S. Kokov (Неотложная медицинская помощь, 2025)
ABSTRACT The results of studies investigating the impact of contralateral carotid occlusion (CCO) in patients with carotid stenosis who have undergone endarterectomy or stenting vary in the literature. We aimed to determine which approach is the optimal revascularization strategy for those patients.THE AIM OF STUDY To review the current scientific literature reflecting the outcomes of patients with CCO and to determine whether the presence of CCO plays a prognostic role in perioperative outcomes in patients undergoing carotid revascularization with endarterectomy or stenting.MATERIAL AND METHODS Literature sources from Pubmed and MEDLINE, Scopus and Cochrane information aggregators on this topic published in Russian and English between 2003 and 2023 were selected for analysis. The terms of contralateral carotid occlusion, stenting of the single carotid artery, carotid endarterectomy, endovascular treatment for stenosis of the single carotid artery, surgery of the single carotid artery, carotid and (stent or stenting) and endarterectomy and (contralateral or bilateral) and occlusion were included in the analysis.An observational or randomized study was considered eligible for inclusion only if it met all specified inclusion criteria: (1) carotid revascularization outcomes were compared in patients with and without CCO; (2) quantitative data on clinical outcomes of interest were provided; and (3) the study was published before September 2023. Studies that did not meet any of these criteria were not eligible for inclusion. Common exclusion criteria were carotid revascularization performed concurrently with coronary revascularization, acutely developing stroke, spontaneous carotid dissection or fibromuscular dysplasia.RESULTS 35 literature sources were analyzed. The review article presents the world experience of surgical treatment (carotid endarterectomy and stenting of the internal carotid artery) in patients with haemodynamically significant stenosis and contralateral carotid occlusion. Some papers indicate the advantages of endovascular operations in elderly patients, others carotid endarterectomy. The accumulation of experience in treatment of this category of patients should help either in optimization or in individualization of surgical tactics.CONCLUSION Surgical intervention in patients with haemodynamically significant stenosis of the internal carotid artery and contralateral occlusion should be differentiated and have an individual approach.